Babesiosis-induced warm autoimmune hemolytic anemia, from infection to hemolysis: a case report - Jenna Davison; Jonah Kan; Jennifer Gile; Ubenthira Patgunarajah; Jeffry Degenhardt; Ronald Go; Jithma P. Abeykoon (Journal of Medical Case Reports)
Abstract Background Warm autoimmune hemolytic anemia is characterized by destruction of red blood cells mediated by autoantibodies, which can be triggered by various underlying factors including tick-borne infections. Babesia spp. are protozoan parasites transmitted by tick bites that cause babesiosis and have been increasingly recognized as a potential precipitating factor for warm autoimmune hemolytic anemia. Case presentation This was a retrospective review of a single case where patient information was extracted from the electronic medical records after written informed consent was obtained. A literature review was also performed. We present a rare case of a 71-year-old White, non-Hispanic/Latino male patient with babesiosis and concurrent warm autoimmune hemolytic anemia. The patient initially presented with fever, chills, and anemia. A tick-borne illness panel was positive for Babesia microti. Despite therapy with doxycycline, azithromycin, and atovaquone, the hemoglobin continued to decline. This prompted investigation for autoimmune hemolytic anemia. A direct antiglobulin test revealed weak positivity for immunoglobulin G. After treatment with high-dose prednisone, the patient’s hemoglobin gradually improved, and his liver enzymes normalized. Conclusions Given the increasing prevalence of tick-borne illnesses, physicians should have a high index of suspicion for concurrent warm autoimmune hemolytic anemia in patients with babesiosis and anemia not improving with typical therapies. In addition, the interplay between babesiosis and warm autoimmune hemolytic anemia underscores the need for clinicians to consider infectious etiologies in the workup of this disease.